Edukasi dan Skrining Kesehatan Berbayar Sampah di Gang Dodol - Ade Saputra Nasution; Alfira Alfira; Annisa Andrea Murdianti; Muhammad Zaki Bagaskara; Tiara Fernanda; Aria Andarista; Ika Kartika; Siti Rahmada Deviah; Noer Puspita Indriani (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
The main focus of the service was to understand and address inequalities in access to health amidst difficult economic conditions. The service objectives include improving the community's understanding of health and providing low-cost health screening services by paying with waste. This service is carried out with health education by counseling and screening, to see the impact of education, interviews are conducted using a questionnaire. The results showed that the community better understood the importance of preventive health. The waste-based health screening program creates a new institution in the payment of health services. The service shows that this creative method can improve access to health and change healthier lifestyles. Potential for sustainable social transformation and community awareness. This study adds to the literature on innovation in community service and paves the way for similar strategies in communities facing similar problems. This program shows great progress towards a healthier and more capable Gang Dodol community.